Biostimulants-induced improvements in pea-barley intercropping systems: A study of biomass and yield optimization under Ukrainian climatic conditions - Bohdan Mazurenko; Md Nasir Hossain Sani; Dmytro Litvinov; Svitlana Kalenska; Vitaliy Kovalenko; Iryna Shpakovych; Olena Pikovska; Lyudmyla Gordienko; Jean Wan Hong Yong; Bhim Bahadur Ghaley; Oksana Tonkha (Journal of Agriculture and Food Research)
The challenge of enhancing crop yields sustainably is critical in modern agriculture. This study investigated the effectiveness of various biostimulants (extracts derived from insect frass, compost, humic material, seaweeds, and fish hydrolysate) on the yield of barley and peas in sole and intercropped systems. Results demonstrated that pea-barley intercrop delivered higher grain yields compared to pea or barley sole crops, with a maximum yield of 7.08 t/ha achieved using compost tea. Barley grain yields in pea-barley intercrop ranged from 4.72 to 5.57 t/ha with biostimulant applications compared to 4.39 t/ha without biostimulant (control) treatment. While pea sole cropping did not show significant yield improvements with biostimulants, intercropped pea yields increased significantly, with humus extract and compost tea enhancing yields by 61.9 % and 45.4 %, respectively. The application of biostimulants also increased the number and weight of seeds per spike in barley and the number of seeds per plant, seed weight per plant, and thousand seed weight in peas. Although intercropping resulted in fewer spikes compared to sole crops, barley produced more grain per spike, with the highest increase observed with seaweed extract. The stimulatory role of biostimulants is associated with their anti-stress action and rhizosphere stimulation for increased N-fixing activity explaining certain increases in productivity, and consequently in the yield of crops, especially in pea-barley intercrop where there is intense competition between species during the generative period of development. Furthermore, the overall land equivalent ratio (LER) for the pea-barley intercropping system was consistently above 1.0, indicating a consistent yield advantage over monoculture throughout the growing season. These findings indicate that biostimulants and intercropping synergistically enhance crop yields and biomass, promoting sustainable agricultural practices by optimizing resource use and minimizing chemical inputs.